Studies of epigenetic cytosine, 5- hydroxymethylcytosine : effects on duplex thermostability and chemical detection methods - Wu, Qiong (2016)
Cytosine methylation is a critical mechanism for epigenetic regulation on the molecular level, which has profound impacts on heritable gene silencing and plays an essential role in mammalian cell development. Recent discoveries suggest that ten eleven translocation proteins (TETs) can oxidize methylcytosine (mC) to generate 5-hydroxymethylcytosine (hmC), 5-formylcytosine (fC), and 5-carboxylcytosine (caC). The molecular mechanism of DNA demethylation and epigenetic regulation system has been revised. Numerous studies focusing at these epigenetic cytosines have been carried out to explore their biological roles. Although a conclusive answer is not yet known, tremendous progress has been achieved from timely developments of technologies that allow for specifically enriching, detecting and sequencing epigenetic cytosines. Genomic sequencing of hmC in genomic DNA reveals that hmC may be associated with both gene expression activation and inhibition, which is considered as a “dual regulation” function. However, it is inconsistent with previous observation that hmC shows only destabilization effect to DNA duplex. In Chapter 2, we have shown that the destabilization effect of hmC on CpG repeats is highly dependent on the overall methylation level of the flanking DNA regions. The phenomena can be observed in either aqueous buffer or crowding condition when either A-form DNA-RNA hybrids or B-form DNA-DNA duplex were investigated. The results provides better understanding of epigenetic regulation via manipulating helical thermostability and may supply knowledge to alternative mechanisms of RNA transcription and intron-exon recognition during mature mRNA formation. As the oxidation product of mC, hmC and fC are proposed to be a key intermediate of active demethylation pathway. Once mC is oxidized to fC, it is recognized and excised by thymine DNA glycosylase (TDG), subsequently restored as normal C with the help of base excision repair (BER) system. To further understand the function of hmC and fC, chemical methods to genomic mapping of fC and hmC would be highly appreciated. In Chapter 3, we have established an effective method to detect fC and hmC in DNA strands. We have found that piperidine and NaOH treatment is able to selectively react with formylcytidine and cause site-specific DNA strand cleavage. Therefore, the position of fC in DNA strand can be profiled by analyzing strand cleavage site. Combine this method with KRuO 4 induced hmC oxidation, sequencing of hmC can be achieved in single base resolution with good selectivity and high efficiency.